2017
DOI: 10.1038/onc.2016.492
|View full text |Cite
|
Sign up to set email alerts
|

The Cdc42/Rac1 regulator CdGAP is a novel E-cadherin transcriptional co-repressor with Zeb2 in breast cancer

Abstract: The loss of E-cadherin causes dysfunction of the cell-cell junction machinery, which is an initial step in epithelial-to-mesenchymal transition (EMT), facilitating cancer cell invasion and the formation of metastases. A set of transcriptional repressors of E-cadherin (CDH1) gene expression, including Snail1, Snail2 and Zeb2 mediate E-cadherin down-regulation in breast cancer. However, the molecular mechanisms underlying the control of E-cadherin expression in breast cancer progression remain largely unknown. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 46 publications
1
56
1
Order By: Relevance
“…Interestingly, CdGAP is required for TGFβ and Neu/ErbB2-induced cell motility and invasion independently of its GAP activity. Through its proline-rich domain, CdGAP forms a functional complex with the transcription factor Zeb2, leading to repression of E-cadherin, and thus favoring epithelial-to-mesenchymal transition (EMT) (54). Another intriguing example is p190B RhoGAP, whose overexpression in the mammary gland results in Rac1 activation and enhanced ErbB2-driven tumorigenesis and metastasis (55).…”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…Interestingly, CdGAP is required for TGFβ and Neu/ErbB2-induced cell motility and invasion independently of its GAP activity. Through its proline-rich domain, CdGAP forms a functional complex with the transcription factor Zeb2, leading to repression of E-cadherin, and thus favoring epithelial-to-mesenchymal transition (EMT) (54). Another intriguing example is p190B RhoGAP, whose overexpression in the mammary gland results in Rac1 activation and enhanced ErbB2-driven tumorigenesis and metastasis (55).…”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…E-cadherin is a key factor in cell-cell adhesion. The destruction of E-cadherin is thought to be one of the first steps in metastasis, playing critical roles in tumor metastasis [21,[31][32][33]. Recent reports have shown that a decrease in E-cadherin is strongly associated with metastasis and poor clinical prognosis and suggested that targeting E-cadherin could be a promising therapeutic approach for metastatic CRC [34].…”
Section: Discussionmentioning
confidence: 99%
“…[35]. ZEB proteins, which are a family of transcription factors, have also been shown to directly bind to the promoter of E-cadherin and suppress its expression at the transcriptional level [21]. DAXX can directly bind to many transcription factors and act as a potent transcriptional repressor [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Of interest, ARHGAP31 has recently been discovered to exhibit transcriptional activity, which is absent in the recurrent p.GlnQ683* nonsense variant, leading to the possibility of potential crosstalk between ARHGAP31 and the Notch signalling pathway. [28] The NOTCH1 extracellular domain is composed of 36 EGF-like repeats, which are modified by posttranslational glycosylation with O-glycan residues. Examination of glycosyltransferase activity in mutant EOGT proteins in vitro has suggested that AOS may be caused by defective O-GlcNAcylation in the endoplasmic reticulum.…”
Section: Notch Signalling In Aosmentioning
confidence: 99%